Pengaruh Efikasi Diri Terhadap Kemandirian Belajar Siswa di SMAN 3 Bukittinggi - Utari Aulia Putri; Alfi Rahmi; Fadhilla Yusri; Sri Hartati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the problem of students’ low self-efficacy. This condition is reflected in students’ lack of confidence when completing difficult tasks, leading them to copy their peers’ work, doubt their own abilities, and give up easily. The lack of self-confidence also causes students to surrender before making an effort, rely on classmates’ answers when assigned tasks, and become dependent on others. Furthermore, low self-belief contributes to students’ limited independence in learning. Therefore, this study was conducted to examine the effect of self-efficacy on students’ independent learning ability at SMA Negeri 3 Bukittinggi. This research employed a quantitative approach with a correlational research design. The population consisted of 380 tenth-grade students, from which 195 respondents were selected through proportional random sampling. Data were collected using questionnaires containing statements related to self-efficacy and learning independence, which had previously been tested for validity and reliability. The collected data were analyzed using simple linear regression analysis. The findings revealed that most students demonstrated high levels of self-efficacy and independent learning. The analysis also indicated a positive relationship between the two variables, implying that the stronger the students’ belief in their own abilities, the higher their tendency to engage in independent learning.